2021
DOI: 10.1140/epjds/s13688-021-00303-9
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of faculty hiring networks

Abstract: Faculty hiring networks—who hires whose graduates as faculty—exhibit steep hierarchies, which can reinforce both social and epistemic inequalities in academia. Understanding the mechanisms driving these patterns would inform efforts to diversify the academy and shed new light on the role of hiring in shaping which scientific discoveries are made. Here, we investigate the degree to which structural mechanisms can explain hierarchy and other network characteristics observed in empirical faculty hiring networks. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
(52 reference statements)
0
9
0
2
Order By: Relevance
“…Analyses of faculty hiring networks, which map who hires whose graduates as faculty, show unambiguously in multiple fields that prestigious departments supply an outsized proportion of faculty, regardless of whether prestige is measured by an extrinsic ranking or reputation scheme [11][12][13] or derived from the structure of the faculty hiring network itself [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Prestigious departments also exhibit 'social closure' 15 by excluding those who lack prestige, facilitated by relatively stable hierarchies over time, both empirically 17 and in mathematical models of self-reinforcing network dynamics 30,31 .…”
mentioning
confidence: 99%
“…Analyses of faculty hiring networks, which map who hires whose graduates as faculty, show unambiguously in multiple fields that prestigious departments supply an outsized proportion of faculty, regardless of whether prestige is measured by an extrinsic ranking or reputation scheme [11][12][13] or derived from the structure of the faculty hiring network itself [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Prestigious departments also exhibit 'social closure' 15 by excluding those who lack prestige, facilitated by relatively stable hierarchies over time, both empirically 17 and in mathematical models of self-reinforcing network dynamics 30,31 .…”
mentioning
confidence: 99%
“…164 Out-of-proportion hiring of White men is never viewed as a racial or gender preference, yet every candidate of color risks being labeled a "diversity hire" in the eyes of some. Network effects exacerbate inequality by amplifying the advantages of privileged groups, 189, [333][334][335][336][337] meaning that those who aren't victimized by systemic discrimination actually benefit from it. The so-called meritocracy frequently devolves into pattern-matching, with a template reflecting the legacy elites who have historically dominated the scientific enterprise.…”
Section: Digital Discovery Accepted Manuscriptmentioning
confidence: 99%
“…Recent years have observed a growing interest in quantifying the faculty hiring process in various fields (Hanneman, 2001;Barnett et al, 2010;Clauset et al, 2015;Cowan and Rossello, 2018;Fernandes et al, 2020;Mai et al, 2015;Zuo et al, 2019;Fowler et al, 2007;Lee et al, 2021;Wapman et al, 2022). For instance, researchers used a network science approach to study the trajectories of 19,000 faculty members in business, computer science, and history (Clauset et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that doctoral program prestige is a strong predictor of faculty placement and that there exists a bias towards men compared with women with the same training, especially in the fields of business and computer science (Clauset et al, 2015). A follow up study in 2021, which used the same data set, utilized adaptive rewiring network models to test mechanisms that give rise to the hierarchical nature of the faculty hiring observed in the 2015 study (Lee et al, 2021). It concludes that a mixture of two mechanisms, total faculty production and local homophily, likely drives the dynamics of real world faculty hiring (Lee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation